2021
DOI: 10.1155/2021/6155304
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Associated Risk Factors in the Elderly Population in Asmara, Eritrea: Results from a Community-Based Cross-Sectional Study

Abstract: Background. The ultimate goal of the study was to approximate the burden and patterns of dyslipidemia in a subset of the elderly population (≥60–85 years) living in Asmara, Eritrea, and to identify modifiable risk drivers. Methods. A total of 319 (145 (45.5%) male vs. 174 (54.5%) female, mean age ± SD (68.06 ± 6.16 years), participants from randomly selected estates within Asm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
4
2
Order By: Relevance
“…Our study shows a higher proportion of reduced HDL in both the included group participants as compared to the findings of the study, revealing higher TGs (58%) in subjects with type 2 diabetes [ 29 ]. Contrary to our findings, another study demonstrated high TC (51.2%) as compared to HDL (28.2%) and TGs (27.6%) among the subjects [ 30 ]. Diet and lifestyle play a key role in affecting health status.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study shows a higher proportion of reduced HDL in both the included group participants as compared to the findings of the study, revealing higher TGs (58%) in subjects with type 2 diabetes [ 29 ]. Contrary to our findings, another study demonstrated high TC (51.2%) as compared to HDL (28.2%) and TGs (27.6%) among the subjects [ 30 ]. Diet and lifestyle play a key role in affecting health status.…”
Section: Discussioncontrasting
confidence: 99%
“…On the basis of currently available data, we believe that a large part of the observed outcome can be explained by physical inactivity and dietary factors. In general, Eritrea's traditional cuisine is starch- rich and emerging evidence supports the notion that sedentarism is a problem in Asmara 18 . Research in runners and the Framingham study demonstrated a strong inverse relationship between HDL-C concentration and physical activity 48 .…”
Section: Discussionmentioning
confidence: 73%
“…“A single population-proportion formula was used to determine the sample size 17 .” Using a proportion of dyslipidemia to be 70% (we used 70% prevalence) 18 , 95% confidence interval (CI), 5% type I error level, 80% power, and design effect of 1.2; the sample size was calculated to be close to 386 participants.…”
Section: Methods and Designmentioning
confidence: 99%
“…Previous studies stated that elderly people with dyslipidemia were at increased risk of CVD events. 30 , 31 Hypercholesterolemia increases the atherosclerosis process leading to the deposition of cholesterol and fatty acids in artery walls, making it at risk for the development of CVD. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies stated that elderly people with dyslipidemia were at increased risk of CVD events. 30,31 Hypercholesterolemia increases the atherosclerosis process leading to the deposition of cholesterol and fatty acids in artery walls, making it at risk for the development of CVD. 32 Our findings highlight the need for policymakers and healthcare providers to develop tailored interventions targeted at the elderly population.…”
Section: Discussionmentioning
confidence: 99%